Protective Mechanism of Gandou Decoction in a Copper-Laden Hepatolenticular Degeneration Model: In Vitro Pharmacology and Cell Metabolomics - Yin, Fengxia; Nian, Mengnan; Wang, Na; Wu, Hongfei; Wu, Huan; Zhao, Wenchen; Cao, Shijian; Wu, Peng; Zhou, An (Frontiers in Pharmacology, 2022)
Gandou decoction (GDD) is a classic prescription for the treatment of hepatolenticular degeneration (HLD) in China, however, the liver-protecting mechanism of this prescription needs further evaluation. In the present study, we explored the protective mechanisms of GDD in a copper-laden HLD model using integrated pharmacology and cellular metabolomics in vitro. The results revealed that GDD could significantly promote copper excretion in copper-laden HLD model cells and improve the ultrastructural changes in hepatocytes. In addition, GDD could decrease the extent of lipid peroxidation (MDA), levels of reactive oxygen species (ROS), and the release rate of lactate dehydrogenase (LDH), while increasing the activity of superoxide dismutase (SOD) and the ratio of glutathione to oxidized glutathione (GSH/GSSG) in copper-laden HLD model cells. On conducting statistical analysis of significant metabolic changes, 47 biomarkers and 30 related metabolic pathways were screened as pharmacological reaction induced by GDD in HLD model cells. D-glutamate and D-glutamine metabolic pathways showed the highest importance and significance among the 30 metabolic pathways, and the differential expression levels of the glutamine synthetase (GS), and renal type and liver type GLS (GLS1 and GLS2) proteins were verified by Western blotting. Collectively, our data established the underlying mechanism of GDD therapy, such as the promotion of copper excretion, and improvement in oxidative stress by regulating the expressions of GS, GLS1 and GLS2 protein to protect hepatocytes from injury.